A rare case of double lumen in the fallopian tube - Jain, Preeti; Jamir, Imtisangla; Mulla, Arsala; Nayak, Sonal (International Journal of Research in Medical Sciences, 2025)
Mullerian duct anomaly is seldom reported in the literature. Isolated congenital anomalies of the fallopian tubes are uncommon and are often overlooked due to the limited data available about this entity. Various other anatomical variations to mention are accessory tubes, sacculations and atresia or segmental deletion of different regions of the tube. The double lumen fallopian tube was observed in a 45-year-old female admitted for complain of menorrhagia for one year. The patient had undergone hysterectomy with right tubal ligation and specimen was send for histopathology section. Histopathological examination revealed double lumen in right fallopian tube. Due to the limited data available and lack of awareness about this entity, it is often overlooked. This report presents a rare anatomical variation in the form of double lumen fallopian tube on the right side.